Symposium 1: Dimensions of identity and the student experience of networked learning - Davis, Jane (Proceedings of the International Conference on Networked Learning, 2014)
The focus of this paper is the conceptualisation of the student identity standard and its potential to impact on the way in which, and the extent to which, non-traditional students engage with learning architectures, particularly those of networked learning communities. It makes a case that often unseen, unperceived, and therefore invisible dimensions of identity, both within and outside the learning community impact on the way that non-traditional students engage with roles within the community and the opportunities afforded through such engagement. The paper briefly introduces the strategic drivers that emphasised the need for increased adoption of technology enhanced learning within higher education and the associated political backdrop as the widening participation agenda was promoted by the Department for Education and Science. It reports the political promotion of flexible learning and the way in which higher education has adapted to an increasing breadth of student backgrounds and life-experiences without necessarily querying the nature of the student role identity. The paper then moves to consider the way in which student identity is of relevance to the learning experience, drawing attention to the concept of role identity (Stryker, 2002) and the individual construction of identity standards (Burke & Stets, 2009). The paper then considers the way in which differing concepts of identity have been explored and addressed in the literature that surrounds networked learning. The paper introduces Cantwell’s conceptualisation of dimensions of student identity (2007) and proceeds to ask the reader to reflect upon on such dimensions of the individually constructed student role identity that are often imperceptible to tutors, peers, and sometimes to the student themselves, and the impact of these dimensions on the networked learning experiences of non-traditional undergraduates. The paper then suggests consideration of the way in which the dynamic and temporal nature of role identities is associated with the concept of affordance and implications for the development and facilitation of learning communities.